The Forgotten Room - White, Karen (Karen S.); Williams, Beatriz; Willig, Lauren (New York : New American Library, 2016)
Dr. Kate Schuyler finds herself drawn into a mystery involving three generations of her family when Captain Cooper Ravenal is brought into the private Manhattan hospital where she works.
Keywords: Women physicians -- Fiction; Physicians -- Fiction; Mothers and daughters -- Fiction; Family secrets -- Fiction; Detective and mystery fiction